Potential of Aqueous Humor as a Surrogate Tumor Biopsy for Retinoblastoma - Berry, Jesse L. (JAMA Ophthalmol, 2017)
IMPORTANCE: Retinoblastoma (Rb) is one of the first tumors to have a known genetic etiology. However, because biopsy of this tumor is contraindicated, it has not been possible to define the effects of secondary genetic changes on the disease course. OBJECTIVE: To investigate whether the aqueous humor (AH) of Rb eyes has sufficient tumor-derived DNA to perform genetic analysis of the tumor, including DNA copy number alterations. DESIGN, SETTING, AND PARTICIPANTS: This investigation was a case series study at a tertiary care hospital (Children’s Hospital Los Angeles) with a large Rb treatment center. Cell-free DNA (cfDNA) was isolated from 6 AH samples from 3 children with Rb, including 2 after primary enucleation and 1 undergoing multiple intravitreous injections of melphalan for vitreous seeding. Samples were taken between December 2014 and September 2015. MAIN OUTCOMES AND MEASURES: Measurable levels of nucleic acids in the AH and identification of tumor-derived DNA copy number variation in the AH. The AH was analyzed for DNA, RNA, and micro-RNA using Qubit high-sensitivity kits. Cell-free DNA was isolated from the AH, and sequencing library protocols were optimized. Shallow whole-genome sequencing was performed on an Illumina platform, followed by genome-wide chromosomal copy number variation profiling to assess the presence of tumor DNA fractions in the AH cfDNA of the 3 patients. One child’s cfDNA from the AH and tumor DNA were subjected to Sanger sequencing to isolate the RB1 mutation. RESULTS: Six AH samples were obtained from 3 Rb eyes in 3 children (2 male and 1 female; diagnosed at ages 7, 20, and 28 months). A corroborative pattern between the chromosomal copy number variation profiles of the AH cfDNA and tumor-derived DNA from the enucleated samples was identified. In addition, a nonsense RB1 mutation (Lys→STOP) from 1 child was also identified from the AH samples obtained during intravitreous injection of melphalan, which matched the tumor sample postsecondary enucleation. Sanger sequencing of the AH cfDNA and tumor DNA with polymerase chain reaction primers targeting RB1 gene c.1075A demonstrated this same RB1 mutation. CONCLUSIONS AND RELEVANCE: In this study evaluating nucleic acids in the AH from Rb eyes undergoing salvage therapy with intravitreous injection of melphalan, the results suggest that the AH can serve as a surrogate tumor biopsy when Rb tumor tissue is not available. This novel method will allow for analyses of tumor-derived DNA in Rb eyes undergoing salvage therapy that have not been enucleated.